Automatic Depuration System for Green Mussels (Perna viridis) to Support Food Safety - Syah, Syalahuddin Abdul Aziz; Suryo, Yoedo Ageng (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
The high content of heavy metals in green mussels necessitates the development of an effective depuration system. Automation of the depuration system becomes a crucial solution to optimize efficiency and effectiveness, both in terms of natural and human resource utilization. This research aims to develop an automated depuration system using an ESP-32 microcontroller integrated with digital filters EMA (Exponential Moving Average) and LPF (Low Pass Filter) to enhance sensor reading stability. The monitored water quality parameters include temperature (DS18B20), pH (4502C), TDS (V1.0), and salinity. Measurement data is displayed in real-time through LCD I2C and stored in an SD Card for continuous recording. System testing was conducted for 24 hours, focusing on sensor performance evaluation and pump activity. The results showed that the automated depuration system operated according to the set parameters without deviation. The sensors demonstrated high accuracy with low error percentages: temperature (0.34%), pH (2.02%), TDS (0.91%), and salinity (5.92%). Implementation of this system resulted in a high mussel survival rate of 95%, proving its effectiveness in the green mussel depuration process.Tingginya kandungan logam berat pada kerang hijau mendorong pengembangan sistem depurasi yang efektif. Otomatisasi sistem depurasi menjadi solusi krusial untuk mengoptimalkan efisiensi dan efektivitas, baik dari aspek pemanfaatan sumber daya alam maupun sumber daya manusia. Penelitian ini bertujuan mengembangkan sistem depurasi otomatis menggunakan mikrokontroler ESP-32 yang diintegrasikan dengan filter digital EMA (Exponential Moving Average) dan LPF (Low Pass Filter) untuk meningkatkan stabilitas pembacaan sensor. Parameter kualitas air yang dipantau meliputi suhu (DS18B20), pH (4502C), TDS (V1.0), dan salinitas. Data pengukuran ditampilkan secara real-time melalui LCD I2C dan disimpan dalam SD Card untuk pencatatan berkelanjutan. Pengujian sistem dilakukan selama 24 jam dengan fokus pada evaluasi kinerja sensor dan aktivitas pompa. Hasil penelitian menunjukkan sistem depurasi otomatis beroperasi sesuai dengan parameter yang ditetapkan tanpa penyimpangan. Tingkat akurasi sensor terbukti tinggi dengan persentase error yang rendah; suhu (0,34%), pH (2,02%), TDS (0,91%), dan salinitas (5,92%). Implementasi sistem ini menghasilkan tingkat kelulushidupan kerang yang mencapai 95%, membuktikan efektivitas sistem dalam proses depurasi kerang hijau.